2019
DOI: 10.1073/pnas.1910471116
|View full text |Cite
|
Sign up to set email alerts
|

Introgression drives repeated evolution of winter coat color polymorphism in hares

Abstract: Changing from summer-brown to winter-white pelage or plumage is a crucial adaptation to seasonal snow in more than 20 mammal and bird species. Many of these species maintain nonwhite winter morphs, locally adapted to less snowy conditions, which may have evolved independently. Mountain hares (Lepus timidus) from Fennoscandia were introduced into the Faroe Islands in 1855. While they were initially winter-white, within ∼65 y all Faroese hares became winter-gray, a morph that occurs in the source population at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(113 citation statements)
references
References 32 publications
4
102
2
Order By: Relevance
“…However, as 351 expected, we see that initial rates of allele frequency change and phenotypic adaptation are 352 considerably faster for a positively selected dominant mutation (Fig. 5B) A growing number of studies have found evidence for convergent adaptation within and between 363 species [8][9][10][11][12]18,58,59], although we often lack an understanding of the forces that determine 364 whether local adaptation occurs through independent de novo mutations or migration of pre-365 existing alleles from other populations [2]. Our study provides rare empirical insights into how 366 gene flow, mutation, allelic dominance, and selection interact to shape the spatial scale and pace 367 of local adaptation to new or changing environments.…”
Section: Migration-selection Balance 338supporting
confidence: 65%
See 1 more Smart Citation
“…However, as 351 expected, we see that initial rates of allele frequency change and phenotypic adaptation are 352 considerably faster for a positively selected dominant mutation (Fig. 5B) A growing number of studies have found evidence for convergent adaptation within and between 363 species [8][9][10][11][12]18,58,59], although we often lack an understanding of the forces that determine 364 whether local adaptation occurs through independent de novo mutations or migration of pre-365 existing alleles from other populations [2]. Our study provides rare empirical insights into how 366 gene flow, mutation, allelic dominance, and selection interact to shape the spatial scale and pace 367 of local adaptation to new or changing environments.…”
Section: Migration-selection Balance 338supporting
confidence: 65%
“…Agouti variant [59]. Collectively, our results suggest that geographic distance and mutational 431 target size, in addition to population structure and history, should play a crucial role in 432 generating hypotheses about the relative roles of independent mutation and gene flow in 433 adaptation.…”
Section: Migration-selection Balance 338mentioning
confidence: 87%
“…A growing number of studies have found evidence for convergent adaptation within and between species (Hoekstra and Nachman 2003;Steiner et al 2008;Rosenblum et al 2010;Dobler et al 2012;Marques et al 2017;Giska et al 2019;Nelson et al 2019;Harris et al 2020), although we often lack an understanding of the forces that determine whether local adaptation occurs through independent de novo mutations or migration of pre-existing alleles from other populations (Ralph and Coop 2015). Our study provides rare empirical insights into how gene flow, mutation, allelic dominance, and selection interact to shape the spatial scale and pace of local adaptation to new or changing environments.…”
Section: Discussionmentioning
confidence: 93%
“…Hybridization among closely related species is hypothesized to enlarge the gene pool of potentially adaptive loci and allow groups to undergo rapid morphological or ecological radiation or range expansion (Abbott et al 2013, Whitney et al 2015, Pfenning et al 2016, Grant and Grant 2019. Examples of specific known genes that have been transferred by hybridization include genes for wing pattern in Heliconius (Pardo-Diaz 2012), flower color in the Diplacus aurantiacus complex (formerly Mimulus aurantiacus; Striesfeld 2015, Stankowski et al 2017), serpentine tolerance in Arabidopsis arenosa (Arnold et al 2016), and winter coat color in various species of hares (Jones et al 2018, Giska et al 2019. In many other cases, hybridization is hypothesized to have allowed species to expand their ranges, although the genes that are responsible have not always been determined (e.g., Cupressus, Ma et al 2019;Populus, Suarez-Gonzalez et al 2017, Chhatre et al 2018.…”
Section: Evolutionary Significance Of Interspecific Gene Flow In Chermentioning
confidence: 99%
“…However, introgression, the presence of a much smaller fraction of the genome of one species in another species, is also of great evolutionary significance (Anderson 1949, Heiser 1973, Rieseberg & Wendel 1993, Arnold 2016. The generation of massive amounts of DNA sequence data through next generation sequencing has led to the recognition of introgression on a scale that was not previously suspected (e.g., Edelman et al 2019, Giska et al 2019.…”
Section: Introductionmentioning
confidence: 99%